Discovery of new pyridine-quinoline hybrids as competitive and non-competitive PIM-1 kinase inhibitors with apoptosis induction and caspase 3/7 activation capabilities - Mostafa M. M. El-Miligy; Marwa E. Abdelaziz; Salwa M. Fahmy; Tamer M. Ibrahim; Marwa M. Abu-Serie; Mona A. Mahran; Aly A. Hazzaa (Taylor & Francis Group, 2023)
New quinoline-pyridine hybrids were designed and synthesised as PIM-1/2 kinase inhibitors. Compounds 5b, 5c, 6e, 13a, 13c, and 14a showed in-vitro low cytotoxicity against normal human lung fibroblast Wi-38 cell line and potent in-vitro anticancer activity against myeloid leukaemia (NFS-60), liver (HepG-2), prostate (PC-3), and colon (Caco-2) cancer cell lines. In addition, 6e, 13a, and 13c significantly induced apoptosis with percentage more than 66%. Moreover, 6e, 13a, and 13c significantly induced caspase 3/7 activation in HepG-2 cell line. Furthermore, 5c, 6e, and 14a showed potent in-vitro PIM-1 kinase inhibitory activity. While, 5b showed potent in-vitro PIM-2 kinase inhibitory activity. Kinetic studies using Lineweaver-Burk double-reciprocal plot indicated that 5b, 5c, 6e, and 14a behaved as competitive inhibitors while 13a behaved as both competitive and non-competitive inhibitor of PIM-1 kinase enzyme. Molecular docking studies indicated that, in-silico affinity came in coherence with the observed in-vitro inhibitory activities against PIM-1/2 kinases.